Programmed cell death and apoptosis — where it came from and where it is going: From Elie Metchnikoff to the control of caspases - Maghsoudi, N.; Zaketi, Z.; Lockshin, R.A. (Experimental Oncology, 2012)
The story of cell death began with the origins of cell biology, including important observations by Elie (Ilya) Metchnikoff, who realized that phagocytes engulfed dying cells. Most of the early studies were observational. By the middle of the 20th C, researchers were beginning to explore how cells died, had recognized that cell death was a physiologically controlled process, that the most common mode of death (“shrinkage necrosis”, later apoptosis) was tightly controlled, and were speculating whether lysosomes were “suicide bags”. Just prior to 1990 several discoveries led to rapid expansion of interest in the field and elucidation of the mechanisms of apoptosis. Closer to the beginning of the 21st C comprehensive analysis of the molecules that controlled and effected apoptosis led to the conclusion that autophagic processes were linked to apoptosis and could serve to limit or increase cell death. Today, realizing that knowledge of the components of cell death has not yet produced pharmaceuticals of therapeutic value, research is turning to questions of what metabolic or other mechanisms indirectly control the activation or suppression of the cell death positive feedback loop. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.